CompTIA Security+ study guide exam SY0-701 - Chapple, Mike 1975-; Seidl, David (Ascent Audio, 2024)
In the newly revised ninth edition of CompTIA Security+ Study Guide: Exam SY0-701, veteran cybersecurity professionals and educators Mike Chapple and David Seidl deliver easy-to-follow coverage of the security fundamentals tested by the challenging CompTIA SY0-701 exam. You'll explore general security concepts, threats, vulnerabilities, mitigations, security architecture and operations, as well as security program management and oversight. You'll get access to the information you need to start a new career-or advance an existing one-in cybersecurity, with efficient and accurate content. You'll also find practice exams that get you ready to succeed on your first try at the real thing and help you conquer test anxiety; hundreds of review questions that gauge your readiness for the certification exam and help you retain and remember key concepts; and complimentary access to the online Sybex learning environment, complete with hundreds of additional practice questions and flashcards, and a glossary of key terms.